x^3 - y^3 + 2x^2 + 2xy
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Không có dấu '' = '' để tìm x nhé.
\([4.\left(x-y\right)^5+2.\left(x-y\right)^3-3.\left(x-y\right)^2];\left(y-x\right)^2\)
\(=[4.\left(x-y\right)^5+2.\left(x-y\right)^3-3.\left(x-y\right)^2]:\left(x-y\right)^2\)
\(=4.\left(x-y\right)^3+2.\left(x-y\right)-3\)
\(=4.\left(x^3-3x^2y+3xy^2-y^3\right)+2x-2y-3\)
\(=4x^3-12x^2y+12xy^2-y^3+2x-2y-3\)
\(x.\left(x^2-4\right)-3x+6\)
\(=x.\left(x+2\right).\left(x-2\right)-3.\left(x-2\right)\)
\(=\left(x^2+2x\right).\left(x-2\right)-3.\left(x-2\right)\)
\(=\left(x-2\right).\left(x^2+2x-3\right)\)
\(=\left(x-2\right).\left(x^2-x+3x-3\right)\)
\(=\left(x-2\right).[x.\left(x-1\right)+3.\left(x-1\right)]\)
\(=\left(x-2\right).\left(x-1\right).\left(x+3\right)\)
\(x^3-y^3+2x^2-2xy\) (Mình sửa đề.)
\(=\left(x-y\right).\left(x^2+xy+y^2\right)+2x.\left(x-y\right)\)
\(=\left(x-y\right).\left(x^2+xy+y^2+2x\right)\)